Cattibal - Lin, Arisa Mei Jie (Nanyang Technological University, 2023)
Cattibal is a 3D online multiplayer battle royale game where players play as blood thirsty cannibalistic cats fighting to be the last cat standing in an abandoned shrine. It is played in first-person perspective and focuses on close combat fighting strategies.